Review of Global Tax Fairness, Thomas Pogge and Krishen Mehta, Editors - Weinzierl, Matthew (Journal of Economic Literature, 2018)
This timely volume (Global Tax Fairness, edited by Thomas Pogge and Krishen Mehta) on the proper taxation of multinational enterprises argues that several feasible, near-term reforms could substantially narrow the scope for tax avoidance by closing information gaps, and it proposes more ambitious, long-term reforms that pursue coordination on the design, not just the enforcement, of tax policy. The editors construct an impassioned normative case that (legal) avoidance violates fairness because its negative effects fall especially hard on the world's poor, but their case could be bolstered by an appeal to the classical benefit-based logic behind the central aim of the reforms they recommend. (JEL D63, F23, H25, H87, K34).